Simulation on the Effect of Coolant Inlet Temperature and Mass-Flowrate Variations to the Temperature Distribution in Single Pellet Thermal Reactor Core - Elin Yusibani; Fitria Helmiza; Fashbir Fashbir; Sidik Permana (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
An important factor in the development of nuclear energy is reactor safety. The performance of heat transfer from nuclear fuel to coolant is the main key to the reactor safety. This paper presents simulation on temperature distribution in two-dimensional laminar flow for single pellet thermal reactor with variation on temperature inlet and mass-flowrate. The OpenFoam platform (SimFlow 3.1) has been used for the computational and numerical analysis. The simulation is carried out on a single pellet with an aspect ratio of 1.2. The variations in the mass velocity of the coolant flow are 10, 100, and 14300 kg×s-1 with a constant coolant temperature of 552 K, and the variations of the input coolant temperature are 300, 552, and 1000 K with a constant mass-flowrate of 10 kg×s-1. The results obtained from the simulation show that for variations in the input coolant temperature of 300, 552, and 1000 K, the fuel temperature can be reduced respectively by 34, 26, and 14 K. At the fastest variation in the coolant mass-flowrate of 14300 kg×s-1, the coolant temperature around the pellet rises by 396 K. The decrease in fuel temperature is significant if the mass-flowrate of the input coolant flow is relatively low.